Implementation of Network and Server Monitoring on Mikrotik with Netwatch Via Telegram Bot - Maestro Pasaribu, Yohanes; Ferdiansyah, Ferdiansyah (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2024)
Computer network is a communication between two or more computers that can exchange information data. The development of a network is supported by adequate devices in that place. When the network has developed, it must be able to periodically monitor all connected network devices. Methodist School 2 conducts online platform-based learning, namely JIA (Jelajah Ilmu Acer) for the junior high, high school and vocational levels. Mehtodist 2 Palembang School uses Mikrotik as its network router, a problem was found that it could not control the network at Methodist School 2 Palembang regularly. This will make it difficult for a network administrator to supervise because they have to control and analyze the performance of their devices and network communications manually. With this problem, the author made an Implementation of Network and Server Monitoring on Mikrotik with Netwatch via Telegram Bot, the author configured several logs that will be integrated into the telegram bot in the Mikrotik tool, Netwatch. The telegram bot will send message notifications about the status of connected devices in the proxy, with this project it is hoped that the author can help network administrators to be able to help control and analyze the network at Methodist School 2 Palembang.